Differences of gut microbiota composition in mice supplied with polysaccharides from γ-irradiated and non-irradiated Schizophyllum commune. (January 2022) - Yin, Chaomin; Qiao, Xin; Fan, Xiuzhi; Chen, Zheya; Yao, Fen; Shi, Defang; Li, Yuhong; Gao, Hong
Graphical abstract: Highlights: N-SFP and I-SFP supplementation prevent body weight gain. I-SFP shows better effects than N-SFP on modulating the mice gut microbiota. Abstract: In this study, polysaccharides from normal (N-SFP) and γ-irradiated (I-SFP) Schizophyllum commune were supplied to Kunming mice for 30 days. The results showed that N-SFP and I-SFP supplementation prevent body weight gain, enhance kidney uric acid metabolism and increase the concentration of SCFAs to a certain extent. Moreover, N-SFP and I-SFP promote the growth of beneficial gut microbiota and inhibit the growth of harmful bacteria. Compared to N-SFP, I-SFP decreased the relative abundance of Muribaculaceae and Lactobacillaceae, and increased the beneficial gut microbiota, especially the family of Akkermansiaceae, Lachnospiraceae and Bacteroidaceae . In total, I-SFP showed better effects than N-SFP in preventing weight gain, and modulating the mice gut microbiota, which suggests that I-SFP could act as a potential health supplement in the prevention of obesity.